NUCLEAR IMAGING IN THE DIAGNOSIS OF CARDIAC AMYLOIDOSIS - V. B. Sergienko; S. N. Tereshchenko; A. A. Ansheles; I. V. Zhirov; A. A. Safiullina (Рациональная фармакотерапия в кардиологии)
Histological analysis of endomyocardial tissue is still the gold standard for the diagnosis of cardiac amyloidosis but has its limitations. Accordingly, there is a need for noninvasive techniques to cardiac amyloidosis diagnostics. Echocardiography and magnetic resonance imaging can show characteristics which may not be very specific for cardiac amyloid. Recently, new opportunities of nuclear imaging in risk stratification and assessment of prognosis for patients with cardiac amyloidosis have appeared. During the last two decades different classes of radiopharmaceuticals have been developed based on compounds tropic to the components of amyloid infiltrates. In this paper we describe the current possibilities and perspectives of nuclear medicine techniques in patients with cardiac amyloidosis, including osteotropic and neurotropic scintigraphy, single-photon and positron emission tomography